Macro (NPK) e micronutrientes (Cu, Zn) no solo em função da aplicação de água residuária de suinocultura - Tonini, Michelle (2018)
Pig production has a global presence significant, adding a large amount of waste that, if not correctly disposed of, can cause severe damage to the environment in the long term. Recognizing this problem, this research evaluated the concentrations of nitrogen, phosphorus and potassium macronutrients, and copper and zinc micronutrients, in the soil after application of swine wastewater (SW), with corn, soybean and oat crops. The experimental area presents a history of SW application of eight years, adding up to 19 vegetative cycles. In this research, the results from cycles 14th to 19th were investigated, resulting in three years of application and six vegetative cycles. The SW dosages used were 0, 100, 200, and 300 m³ ha-1 in the cycle, with and without addition of the chemical adduction recommended, with three replicates per treatment, resulting in eight treatments. Soil collection for chemical characterization was carried out before the implantation of each crop and after harvest. The experiment was design as randomized blocks in factorial scheme of 4 x 2, defining as factors the four SW application rates and recommended fertilization (present or absent). For the Zn concentration in soil, over time, linear models of increment were built, regarding the SW application cycle for each treatment. The N, P, K, and Cu data, which did not show significance in the models, were submitted to the Shapiro-Wilk normality test, variance analysis (ANOVA), and had their averages compared through Tukey testing at 5% probability. The results showed there was an increase in macronutrients P and K in the cycles, especially when associated to mineral fertilization. For the copper and zinc contents, an increase was observed as a function of the applied doses and accumulation over time, especially to zinc, both of which exceeded the agronomic limits indicated.